Hormone Replacement Therapy in Rheumatoid Arthritis - Forsblad d'Elia, Helena; Carlsten, Hans (Current Rheumatology Reviews, 2006)
Rheumatoid arthritis (RA) is a common inflammatory rheumatic disease affecting 2-3 times more women as compared to men. The peak incidence of RA in women coincides with the years around menopause when the production of estradiol (E2) and progesterone diminishes. The course of RA is also influenced by hormonal changes. The condition often ameliorates during pregnancy followed by flares after delivery. Animal studies have revealed distinct beneficial effects on arthritis by E2. Studies of hormone replacement therapy (HRT) in postmenopausal RA have disclosed improvement in bone mineral density (BMD) and recently also beneficial effects on disease activity was found. However, in view of side effects by conventional HRT, its use has to be individualized for any given patient and there is a need for new therapeutic agents selectively inducing potent anti-arthritic and anti-inflammatory effects, but without the adverse effects associated with HRT. This review will discuss: - Hormonal factors and gender associated with RA. - Sex hormones and the influence on the immune system and bone. - The effects of treatment with sex hormones on disease activity in RA. - The effects of HRT on BMD and bone and cartilage turnover in RA.
Keywords: osteoporosis